Kinetic drying experimental data and mathematical model for sweet cherries (prunus avium) - Mabellini, Alejandra (2010)
Models for, food particles, dryers design should be as simple as possible. A Dryer can be visualised as formed by a number of thin layers beds, ideally one-particle deep. Therefore, thin layer dehydration studies become essential as a step for developing methods for industrial equipment design. In this work, drying curves were experimentally determined for sweet cherry fruits, using air temperatures of 50, 60, 70 and 80 °C; air relative humidities of 5 and 50 % and air velocities of 1, 2, 3 and 5 m/s. A short time analytical predictive model for diffusion inside solids- fast to run on the computer- was selected to interpret the data with satisfactory accuracy. By this fitting procedure, diffusion coefficients of water in sweet cherries were determined to vary between 6.814 10-11 (50 ºC) and 3.474 10-10 (80 °C) m2/s. The relationship of diffusivities with temperature was accounted for by using an Arrhenius-type equation.